(untitled) (Development Service Industry Management, 2023)
The article examines the definition of “marketing tools”. By marketing tools for business we mean the set of strategies, methods, and tactics to achieve goals and ensure successful interaction with their target audience. The existing marketing tools offered by different authors are presented. Different types of digital marketing tools have been identified and their characteristics have been defined, including their division into: SEO tools (tools that enhance the visibility of a website in search results through search engine optimization), content tools marketing (help to create, expand and improve the effectiveness of content, that attracts and retains the attention of the audience), Growth Hacking tools (tools that capture a large client base, and actively explore different methods (innovative and experimental) to attain business growth), CRM tools (customer relationship management systems allow to monitor and analyze interactions between customers and the company), tools for targeted and contextual advertising (provide assistance to businesses and marketers in directing their advertising messages to a specific audience), influencer- or influx marketing tools (tools for searching, comparing and measuring of results with influx individuals or influencers for promotion of their goods or services). SEO tools include: Google Analytics, Google Search Console, SEMrush, Ahrefs, Moz Pro, Screaming Frog SEO Spider, BuzzSumo, Rank Tracker, AccuRanker, DeepCrawl, Sitebulb. Content marketing tools include: WordPress, Drupal, Joomla, Adobe Creative Suite, Hootsuite, CoSchedule, Asana, Trello, Monday.com. Growth Hacking tools include: Optimizely, HubSpot, Marketo, Hotjar, Crazy Egg, OptinMonster, Social Media (Facebook, Twitter, Instagram, LinkedIn), Video (YouTube, TikTok). CRM tools include: Salesforce, Zoho CRM, Microsoft Dynamics 365, Pipedrive, SugarCRM, Capsule CRM. Targeted and contextual advertising tools include: AspireIQ, Upfluence, Traackr, Influencity, GRIN, Emplifi, Influence.co, Famebit, Hootsuite. The article provides a description of all the listed instruments.